Design and investigation of block copolymers for dispersion of carbon nanotubes in polymer matrices - Liu, Chengyin (2018)
Single-walled carbon nanotubes (SWNTs) are promising nanofillers for synthesizing lightweight, strong polymeric nanocomposites because of their large aspect ratios, low densities, and exceptional mechanical, electrical, and thermal properties. To fully utilize the remarkable properties of SWNTs to mechanically reinforce polymers, investigators’ should focus on nanotube properties such as their content, dispersibility, matrix-interfacial adhesion, and alignment. This thesis focuses on the dispersion and functionalization of SWNTs for mechanical reinforcement of the polymer matrices polyimide (PI) and epoxy (EP). In the first study, poly(amic acid) with sulfone groups complexed with chromium and carbon nanotubes (CNTs), labelled as PAAS-Cr-CNT, was synthesized and shown to be effective in increasing the interaction and interfacial bonding between poly(amic acid) and CNTs compared with traditional non-covalent functionalization, as evidenced by FE-SEM and mechanical testing. The modulus of the composite film increased by up to 35% with 2 wt% CNT loading, and its strength could still be maintained compared to the pure polyimide matrix. However, the dispersion of CNTs was not optimum because of the interaction of chromium with multiple SWNTs during the reaction. To eliminate the interaction issue and further improve the dispersion of CNTs, a triblock copolymer system was introduced. Polycaprolactone-polyimide-polycaprolactone (PCL-PI-PCL) was first synthesized and used to disperse SWNTs in a low boiling point solvent (here we used tetrahydrofuran, THF) and fabricate the composite with epoxy resin. This triblock copolymer has good solubility and are highly effective in dispersing SWNTs in THF, as determined using UV−vis−NIR spectra-photometer, visual observation, and TEM, whereas the PI homopolymer was not so effective in these aspects. For composite processing, new polymers are needed to disperse CNTs in common organic solvents. The synthesized PCL-PI-PCL triblock copolymer dispersed SWNTs (2 wt%) increased the tensile strength, modulus, and elongation at maximum stress by 74%, 35%, and 62%, respectively, as compared to the neat resin blend. As a control comparison, when only the dispersing agent is added to the epoxy resin, the overall tensile properties of the resin decreased. To further improve the tensile properties of the SWNTs/epoxy nanocomposites, we fabricated another series of PI-derived block copolymers via ring-opening polymerization initiated from hydroxyl-terminated polyimide of lactide and allyl-bearing 2-methyl-2-(allyloxycarbonyl)propylene carbonate) (MAC) to produce PLA-b-PI-b-PLA (TB1) and PMAC-b-PI-b-PMAC (TB2) which are polyester and poly(ester-carbonate)-derived, respectively. The allyl pendant group allows facile functionalization and we successfully made the third series of the epoxidized derivative of TB2, i.e. PMACEP-b-PI-b-PMACEP (TB3). We dispersed SWNTs in epoxy resin using these copolymer dispersants and evaluated the mechanical properties of the composite films. The optimal copolymer dispersant (TB3b), which has epoxy groups on the end blocks, can disperse 2% loading of SWNTs and the tensile strength, modulus, and elongation at maximum stress of the composite film increased by 40%, 34%, and 26%, respectively compared to neat epoxy resin. This new synthesis route of the triblock copolymer is applicable to diverse PI-based triblock copolymers with various desired functionalities. By introducing the allyl functional groups, the polymer can further react with other materials where the functional groups can then be easily changed to other functional groups. The main achievement of this thesis is that we first apply chromium complexed SWNTs in polyimide composite films and get a reinforcement in the mechanical properties, especially in modulus. Also, we design a series of triblock copolymers as polymer dispersants for carbon nanotube nanocomposites. The triblock copolymers have good solubility even in low boiling point solvent, and can achieved stable and homogenous CNT dispersion.